Evaluating the Traffic Noise Levels at Median U-Turns under Heterogeneous Traffic Conditions in Makassar City - Hustim, Muralia; Alimuddin, Hardianti; Syafruddin, Nurul Azizah; Andarani, Pertiwi; Ramli, Muh. Isran; Hassan, Sitti Asmah (Engineering, Technology & Applied Science Research, 2025)
This study examines the effect of the traffic noise levels in the presence of Median U-Turns (MUTs). Using quantitative research methods, a Sound Level Meter (SLM) was employed to take direct measurements at 30 sampling points in five major roads of Makassar City. The field measurements revealed that the noise levels consistently exceeded 75 dB, surpassing the national noise limit of 70 dB. Motorcycles dominated (65%) that noise, while heavy vehicles contributed up to 9% according to the traffic composition analysis. It was found that the MUT width, vehicle volume, and speed variations contributed to the elevated noise levels. Metro Tanjung Street exhibited lower noise levels due to the presence of fewer heavy vehicles, despite having a larger vehicle volume than that of wider roads, like Pettarani Street. Most vehicles at speeds below 30 km/h contributed to increased noise. The ASJ-RTN 2008 noise level prediction model showed that locations with MUTs had noise levels that were 7–10 dB higher. The model exhibit strong accuracy with an RMSE of 2.13 dB. This study highlights the significant role of the MUT design, traffic flow, and vehicle composition in influencing the urban noise generated.